Studies on the Standardization of Avalehas; Pugakhanda and Saubhagyasunthi - Santosh, M.K.; Shaila, D.; Sanjeeva Rao, I. (Asian Journal of Chemistry, 2016)
The present paper deals with the standardization of avalehas such as pugakhanda and saubhagyasunthi which was achieved by organoleptic study, physico-chemical analysis, qualitative organic and inorganic analysis, thin layer chromatography (TLC), UV-Visible spectrophotometry and high performance liquid chromatographic (HPLC) fingerprint study. Qualitative organic analysis showed the presence of alkaloids, steroids, phenols, tannins, glycosides, resins, saponins and flavonoids in both pugakhanda and saubhagyasunthi. Qualitative inorganic analysis of pugakhanda revealed the presence of calcium, magnesium and iron whereas saubhagyasunthi showed the presence of aluminum in addition to calcium, magnesium and iron. TLC study of alcoholic extracts of pugakhanda and saubhagyasunthi was carried out in toluene : ethyl acetate solvent system. Alcoholic extracts of both the avalehas were used for UV-Visible spectrophotometry and HPLC fingerprint study. The quantification of gallic acid in pugakhanda and saubhagyasunthi was evaluated using standard gallic acid by HPLC fingerprint study.